2022
DOI: 10.3390/plants11101280
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Constituents and Antiproliferative Activities of Essential Oils from Four Varieties of Malaysian Zingiber officinale Roscoe against Human Cervical Cancer Cell Line

Abstract: This study evaluates the volatile metabolic constituents and anticancer potential of essential oils distilled from the rhizomes of four Malaysian Zingiber officinale Roscoe (Zingiberaceae family) varieties (Bentong (BE), Cameron Highlands (CH), Sabah (SA), and Bara (BA)). The ginger essential oils were analyzed by gas chromatography coupled with quadrupole mass spectrometry (GC qMS). A total of 58 secondary compounds were tentatively identified, representing 82.6–87.4% of the total ion count. These metabolites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Decreased tumor volume and weight with treatment reflect the anti-proliferative efficacy of ginger oil, which was further improved by the nano preparation. Similarly, previous studies reported the antiproliferative effect of ginger oil on various types of cancer [22,60,61].…”
Section: Experimental Study Of Ginger Oil and Ginger Oil Nanoemulsion...supporting
confidence: 55%
See 1 more Smart Citation
“…Decreased tumor volume and weight with treatment reflect the anti-proliferative efficacy of ginger oil, which was further improved by the nano preparation. Similarly, previous studies reported the antiproliferative effect of ginger oil on various types of cancer [22,60,61].…”
Section: Experimental Study Of Ginger Oil and Ginger Oil Nanoemulsion...supporting
confidence: 55%
“…Many researchers studied the effect of ginger against different types of cancer cells. Zaid et al studied the effect of ginger oil on the human cervical cancer cell line, and they found that the oil demonstrated a strong antiproliferation potential [22]. Also, Zhang et al concluded in their study that ginger produced preventive effects against colon cancer [23].…”
Section: Introductionmentioning
confidence: 99%
“…Zingiberaceae plants contain many complex volatiles, some of which are still unknown. In recent years, based on the non-targeted volatilomics approaches, a total of 58 secondary compounds were tentatively identified in four Malaysian Zingiber officinale Roscoe, and 130 metabolites were detected from seven common Zingiberaceae plants [ 36 ]. In this study, by integrating MS2 spectral tag library, we not only improved the method sensitivity but also broadened the annotation coverage and detected and annotated more compounds compared to previous reports in Zingiberaceae plants.…”
Section: Discussionmentioning
confidence: 99%
“…Ginger and its phytoconstituents have also been effective against other cancers such as ovarian [ 158 ], colon [ 146 ], non-small lung [ 159 ], lung [ 159 ], gastric adenocarcinoma [ 160 ], melanoma [ 161 ], and cervical [ 162 ] by modulating NF-κB, p21, ERK1/2, p38, p53, Wnt/ß-catenin, and AMPK. Gingerols were also found to be effective in preventing emesis caused by chemotherapies [ 147 ].…”
Section: Plant-based Food Componentsmentioning
confidence: 99%